Getting at the essence of the administrative state - Caiden, Gerald, E (1991)
Gerald E. Caiden, in this article makes a comprehensive survey of the progress made over the years in conceptualisation of the `Administrative State'. He briefly, but with requisite clarity, identifies twenty-five theories that have been put forward on this subject by scholars. Since all of these are mutually supportive, Caiden's survey greatly helps in streng-thening our understanding of the theoretical constructs that are relevant in comprehending the reality called `Administrative State'. Reproduced
Keywords: Administrative State; Public Administration